Finding Flicker: Critical Differences in Temporal Frequency Capture Attention - Cass, John; Van der Burg, Erik; Alais, David (Frontiers in Psychology, 2011)
Rapid visual flicker is known to capture attention. Here we show slow flicker can also capture attention under reciprocal temporal conditions. Observers searched for a target line (vertical or horizontal) among tilted distractors. Distractor lines were surrounded by luminance modulating annuli, all flickering sinusoidally at 1.3 or 12.1 Hz, while the target’s annulus flickered at frequencies within this range. Search times improved with increasing target/distractor frequency differences. For target-distractor frequency separations > 5 Hz reaction times were minimal with high frequency targets correctly identified more rapidly than low frequency targets (~400ms). Critically, however, at these optimal frequency separations search times for low and high frequency targets were unaffected by set size (slow flicker popped out from high flicker, and vice versa), indicating parallel and symmetric search performance when searching for high or low frequency targets. In a ‘cost’ experiment using 1.3 and 12.1 Hz flicker, the unique flickering annulus sometimes surrounded a distractor and, on other trials, surrounded the target. When centred on a distractor, the unique frequency produced a clear and symmetrical search cost. Together, these symmetric pop-out and search costs demonstrate that temporal frequency is a pre-attentive visual feature capable of capturing attention, and that it is relative rather than absolute frequencies that are critical. The shape of the search functions strongly suggest that early visual temporal frequency filters underlie these effects.